Exploring gunshot residue detection in fingerprints by functionalized particle-coupled matrix-assisted laser desorption/ionization mass spectrometry - Adav, Sunil S. (2024)
In firearm forensic investigations, detecting gunshot residue (GSR) is crucial for linking firearms to suspects and determining firing distance for forensic reconstruction. Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-ToF-MS) is emerging as a versatile and promising technological platform for fingerprint analysis. The capability of functionalized particles as an advanced dusting powder for visualizing latent fingerprints is widely recognized. This study aims to investigate the feasibility of employing functionalized magnetic fingerprint dusting powders for distinguishing regular and GSR fingerprints using MALDI-ToF-MS, thereby enhancing forensic evidentiary support. In this study, silica and carbon coated magnetic iron oxide particles were surface functionalized with phenyltriethoxy orthosilicate (PTEOS) or 3aminopropyl triethoxysilane (APTES) to create hydrophobic and hydrophilic particles, respectively. Donor shooters' fingerprints, both GSR-containing and regular, were analyzed using these functionalized particles coupled with MALDI-ToFMS. The results demonstrated effective fingerprint visualization and conclusive discrimination between GSR-containing and regular fingerprints through orthogonal partial least squares discriminant analysis. This technique provides enhanced sensitivity, speed, and adaptability compared to conventional methods, making it a promising choice for initial detection of GSR in latent fingerprints. Moreover, when subjected to thorough analysis using advanced instruments, it has the potential to significantly strengthen the probative value of fingerprint evidence in forensic investigations.